2020
DOI: 10.3390/ijms21031075
|View full text |Cite
|
Sign up to set email alerts
|

RasGRP2 Structure, Function and Genetic Variants in Platelet Pathophysiology

Abstract: RasGRP2 is calcium and diacylglycerol-regulated guanine nucleotide exchange factor I that activates Rap1, which is an essential signaling-knot in “inside-out” αIIbβ3 integrin activation in platelets. Inherited platelet function disorder caused by variants of RASGRP2 represents a new congenital bleeding disorder referred to as platelet-type bleeding disorder-18 (BDPLT18). We review here the structure of RasGRP2 and its functions in the pathophysiology of platelets and of the other cellular types that express it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 101 publications
0
29
0
Order By: Relevance
“…18,19 From 2001, the year in which P2RY12 was first characterized, 10 newly identified genes include FERMT3, ANO6, RASGRP2 and EPHB2 thereby expanding the gene repertoire for IPD. 25,26,33,34,36,43 The development of next-generation sequencing platforms targeting IPD genes, 6,88 together with widening access to whole exome sequencing, 4,7,8 and now whole genome sequencing, 9 has both increased the number of patients with a genetic diagnosis and the speed at which this is performed. The multiplication of data has underlined the great diversity of variants responsible for gene dysfunction, the rarity of hot-spot mutations, the frequency of compound heterozygosity within the same gene (limiting the notion of consanguinity for recessive diseases); and raised the likelihood of additive effects of heterozygous variants on different genes modulating the phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 From 2001, the year in which P2RY12 was first characterized, 10 newly identified genes include FERMT3, ANO6, RASGRP2 and EPHB2 thereby expanding the gene repertoire for IPD. 25,26,33,34,36,43 The development of next-generation sequencing platforms targeting IPD genes, 6,88 together with widening access to whole exome sequencing, 4,7,8 and now whole genome sequencing, 9 has both increased the number of patients with a genetic diagnosis and the speed at which this is performed. The multiplication of data has underlined the great diversity of variants responsible for gene dysfunction, the rarity of hot-spot mutations, the frequency of compound heterozygosity within the same gene (limiting the notion of consanguinity for recessive diseases); and raised the likelihood of additive effects of heterozygous variants on different genes modulating the phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…CalDAG-GEFI deficiency primarily affects platelet activation induced by low-dose agonist activation involving the first wave of activation. 21 This type of response may also correspond to abnormalities in the amplification pathway mediated by ADP. Reduced response to ADP even at high concentrations (100 μM) has been observed in severe homozygous P2Y12 deficiency [22][23][24][25] (►Table 1).…”
Section: Light Transmission Platelet Aggregationmentioning
confidence: 99%
“…The associated bleeding disorder has been referred to as bleeding disorder platelet-type 18 (BDPLT18). 3 Altogether, more than 20 human disease-causing genetic RASGRP2 variants have been reported up to today. 3,4 In the first description of mutant RasGRP2, Canault et al reported an abolished Rap1 activation in patient platelets upon stimulation, indicating defective platelet aggregation.…”
Section: Introductionmentioning
confidence: 99%
“…3 Altogether, more than 20 human disease-causing genetic RASGRP2 variants have been reported up to today. 3,4 In the first description of mutant RasGRP2, Canault et al reported an abolished Rap1 activation in patient platelets upon stimulation, indicating defective platelet aggregation. 5 In contrast, other platelet activation mechanisms including protein kinase C and adenosine diphosphate (ADP) dependent pathways were not affected by RASGRP2 mutations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation